Impact of the COVID-19 Pandemic on Patients and Staff in Radiation Oncology Departments in Belgium: A National Survey - Vaandering, Aude; Ben Mustapha, Selma; Lambrecht, Maarten; Van Gestel, Dirk; Veldmeman, Liv (Frontiers in Oncology, 2021)
Purpose: COVID-19 reached Belgium in February and quickly became a major public health challenge. It is of importance to evaluate the actual impact of COVID-19 on patients and staff in Belgian radiotherapy departments (RTDs). This was evaluated through a weekly national survey sent to departments measuring key factors that were affected by the pandemic. Materials and methods: The Belgian SocieTy for Radiation Oncology (BeSTRO) together with the Belgian College for physicians in Radiation Oncology invited all 26 RTD to participate in a survey that started on March 2nd and was re- submitted weekly for 4 months to assess variations in time. The survey focused on: 1) the COVID-19 status of patients and staff; 2) the management of clinically suspected COVID patients and COVID positive patients; 3) the impact of COVID-19 on RTD activities; 4) its impact in radiotherapy indications and fractionation schemes. Results: Seventy-three percent of 26 RTDs completed the first survey and 57% responded to all weekly surveys. In the RTD staff, 24 members were COVID-positive of whom 67% were RTTs. Over the study period, the number of patients treated dropped by a maximum of 18.8% when compared to March 2nd. In 32.3% of COVID-positive and 54% of COVID suspected patients, treatment was continued without any interruptions. Radiotherapy indications were adapted within the first weeks of the survey in 47.4% of RTD, especially for urological and breast tumours. Fractionation schemes were changed in 68.4% of RTD, mainly for urological, breast, gastro-intestinal and lung tumours. Conclusions: Between March and June 2020, the COVID-19 pandemic resulted in an important decrease in treatment activity in RTD in Belgium (18.8%). The COVID-19 infection status of patients influenced the continuity of the radiotherapy schedule. Changes in indications and fractionation schedules of radiotherapy were rapidly incorporated in the different RTD.